LC-ESI-MS/MS Simultaneous Analysis Method Coupled with Cation-Exchange Solid-Phase Extraction for Determination of Pyrrolizidine Alkaloids on Five Kinds of Herbal Medicines. (23rd July 2021) - Jeong, Se Hee; Choi, Eun Young; Kim, Jonghwan; Lee, Chulhyun; Kang, Juhye; Cho, Sooyeul; Ko, Kyung Yuk
Abstract: Background: Pyrrolizidine alkaloids (PAs) are naturally occurring plant toxins associated with potential hepatic and carcinogenic diseases in humans and animals. The concern over PAs has increased as the consumption of herbal medicines has increased. Objective: This study aimed to develop and validate a sensitive analytical method to determine 28 PAs in five herbal medicines using liquid chromatography (LC)-electrospray ionization (ESI)-tandem mass spectrometry (MS/MS). Additionally, this study identified and quantified the amount of PAs in 10 samples of each herbal medicine. Methods: The pretreatment in the proposed LC-MS/MS analysis comprised solvent extraction using 0.05M H2 SO4 in 50% methanol and clean-up step using an mixed-mode cationic exchange (MCX)-solid-phase extraction (SPE) cartridge. The PA contents in herbal medicines were measured by using the developed method. Results: The proposed method had recoveries ranging from 72.5–123.7% for the Atractylodis Rhizoma Alba, 70.6–151.7% for Alba Chrysanthmi Flos, 80.6–130.9% for Leonuri Herba, 70.3–122.9% for Gastrodiae Rhizoma, and 67.1–106.9% for Glycyrrhizae Radix. Even though a few samples showed recoveries in unsatisfactory values, the proposed method indicated entirely sufficient recoveries and precision in most samples. In monitoring results, only Leonuri Herba contained two PAs, which indicated Retrorsine (4/10) of 84.7–120.9 μg/kg and Senkirkine (10/10) of 60.9–170.7 μg/kg. Conclusion: The results obtained from this study demonstrate that the proposed method is fit for purpose to determine 28 PAs in herbal medicines. Therefore it could serve as a regulatory method capable of being used for controlling the risks of PAs in certain medicinal plants and dietary supplements. Highlights: An LC-MS/MS method for the determination of 28 pyrrolizidine alkaloids in herbal medicines was developed and validated through this study. The proposed method is considered as an useful method for monitoring pyroolizidine alkaloids in herbal medicines.